2017
DOI: 10.1016/j.ijggc.2017.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of absorber intercooling for CO 2 absorption from natural gas fired flue gases using monoethanolamine solvent

Abstract: 8Chemical absorption using aqueous amine is one of the most feasible options for post-combustion 9 CO 2 capture. One of the main challenges of this technology is its high energy requirements. Absorber 10 intercooling was considered as a viable method to offer benefits in terms of solvent absorption 11 capacity and mass transfer efficiency in CO 2 absorption processes. However, the effectiveness of 12 absorber intercooling on overall energy requirements depends on other factors such as lean loading 13 and liqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 20 publications
(2 reference statements)
1
23
0
Order By: Relevance
“…Different process configurations such as absorber inter-cooling [10], stripper inter-heating [11], rich solvent splitting [12], stripper overhead compression [13], lean vapor compression (LVC) [14], rich vapor compression [14] and many other process modifications have been reported to reduce the energy penalty of the process. Dmartiz et al [15] compared the energy consumption of various amine absorption process configurations and concluded that improvement to the configuration has substantial potential to improve the energetic efficiency of the process.…”
Section: Nomenclature Aimentioning
confidence: 99%
“…Different process configurations such as absorber inter-cooling [10], stripper inter-heating [11], rich solvent splitting [12], stripper overhead compression [13], lean vapor compression (LVC) [14], rich vapor compression [14] and many other process modifications have been reported to reduce the energy penalty of the process. Dmartiz et al [15] compared the energy consumption of various amine absorption process configurations and concluded that improvement to the configuration has substantial potential to improve the energetic efficiency of the process.…”
Section: Nomenclature Aimentioning
confidence: 99%
“…Absorber intercooling can improve column performance by increasing the thermodynamic driving force for mass transfer and reducing the magnitude of the temperature bulge 21 . Intercooling has been investigated for postcombustion capture from coal 22 and natural gas power plants, 23 and for a range of solvents including MEA, 24 pipperazine, 25 and potassium carbonate 26 . Oko et al 27 recently demonstrated that intercooling is essential for rotating bed absorbers utilizing concentrated (70 wt%) MEA solutions, and discussed a range of process configurations.…”
Section: Introductionmentioning
confidence: 99%
“…A description of the chemical absorption that takes place in a PCC system can be achieved by modelling, using either an equilibrium or rate-based mass-transfer, with a number of studies being validated against pilot plant data [9,12,[22][23][24]. Rate-based simulations can provide a greater accuracy and allow a more informed evaluation of the process [12,14,17,[23][24][25][26] but equilibrium approaches can still be employed for process assessment [11,19,27,28]. The relative simplicity of an equilibrium approach and the ability to improve the accuracy of such a model with stage efficiencies [16,19,[29][30][31] is the justification for employing such a strategy here.…”
Section: Introductionmentioning
confidence: 99%